Auditory comprehension performance of college students with and without sport concussion on Computerized-Revised Token Test Subtest VIII. (8th May 2017) - Salvatore, Anthony P; Cannito, Michael; Brassil, Heather E; Bene, Edina R; Sirmon-Taylor, Bess
Aim: Auditory comprehension (AC) and visually assessed cognitive functions were compared in early stage postconcussed (PC) athletes and healthy controls using the Subtest VIII of the Computerized-Revised Token Test (C-RTT) and Immediate Postconcussion Assessment and Cognitive Test (ImPACT).Results: As compared with healthy controls (n = 30), PC subjects (n = 30) had significantly lower C-RTT efficiency scores (p = 0.018), and lower ImPACT scores; total symptom score (p = 0.000.), verbal memory (p = 0.000), visual memory (p = 0.000), visual motor speed (p = 0.000) and reaction time (p = 0.004) in this post-test only matched subject design. Impulse Control was not significant (p = 0.613). Multiple regression and ANOVA indicated an association with reaction time only (p = 0.012) for the PC subjects. After controlling for reaction time, a significant difference in AC remained.Conclusion: The relationship between AC and other visually assessed cognitive functions was inconsistent suggesting that the C-RTT and ImPACT assessed different functional systems.